Конвективна дифузія у двошаровому фільтрі - Чапля, Є.Я.; Чернуха, О.Ю.; Сівак, В.М. (Видавничий дім "Академперіодика" НАН України, 2007)
For constructing the analytical solutions of contact boundary-value problems of convective diffusion, a method based on the application of integral transformations separately in contacting regions is generalized. The admixture concentration in each structural element, as well as mass fluxes and the filter saturation time by a polluting substance, is found.